Women in Modern Society and Job Difficulties - Aida Mehrad Mohammad Hossein Tahriri Zangeneh (Universitas Ahmad Dahlan, 2015)
AbstractÂ Job assumed as one of the main human needs that has great contribution in presence of women in society. The purpose of present literature review is to identify the vital role of job among women at modern society, because it can expand and develop the abilities of women toward society and increase the amount of their responsibilities and performances at work environment. This study also emphasized that job advances the amount of efficiency among womenduring of working. Indeed, this paper supported the need of women to achieve improvement and creative job at society and appear as active member at work.Furthermore, lack of attention to accurate job for women leads to some difficulties for them and decrease their motivation for continuing job and presence at society.Â Keyword: Women, Modern Society, Job difficulties.